Photonic Wire Bonding as a Novel Technology for Photonic Chip Interfaces - Lindenmann, Nicole (KIT Scientific Publishing, 2018)
To create photonic multi-chip modules, integrated photonic chips need to be connected internally and to external glass fibers. A novel approach to address this task is the concept of photonic wire bonding, where free-standing polymer waveguides are printed in-situ by two-photon polymerization. This book contains a detailed description of the methodology of photonic wire bonding together with a number of key experiments.
English
Keywords: optische Aufbau- und Verbindungstechnik; Photonic Wire Bonding; optical interconnects; photonic integrated circuits; integrierte Photonik; Silizium-Photonik; silicon photonics; photonic wire bonding